Archaeological explorations in Syria 2000-2011 : proceedings of ISCACH-Beirut 2015 - Massih, Jeanine Abdul; Nishiyama, Shinichi; Charaf, Hanan; Deb, Ahmad (Archaeopress Publishing Ltd, 2018)
Syria has been a major crossroads of civilizations in the ancient Near East since the dawn of human kind. This volume brings together scholars involved in archaeological activities in Syria and focusses on the scientific aspects of each explored site, allowing researchers to examine in detail each heritage site, its characteristics and identity.